2018
DOI: 10.1051/matecconf/201816514002
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength characterization of Al-Si cast material incorporating statistical size effect

Abstract: Abstract. Cast aluminium components may exhibit material imperfections such as shrinkage and gas pores, or oxide inclusions. Therefore, the fatigue resistance is significantly influenced by the size and location of these inhomogenities. In this work, two different specimen geometries are manufactured from varying positions of an Al-Si-Cu alloy casting. The specimen geometries are designed by means of shape optimization based on a finite element analysis and exhibit different highly-stressed volumes. The numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…Furthermore, to characterize not only the fracture-initiating defects by means of fractography, selected specimens are investigated non-destructively with X-ray computed tomography (XCT). This methodology supports the holistic characterization of the defect population respectively its spatial extent and is further described in [22,48]. Figures 9 and 10 show a fracture surface with a crack origin at a micro pore.…”
Section: Fatigue Testssupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, to characterize not only the fracture-initiating defects by means of fractography, selected specimens are investigated non-destructively with X-ray computed tomography (XCT). This methodology supports the holistic characterization of the defect population respectively its spatial extent and is further described in [22,48]. Figures 9 and 10 show a fracture surface with a crack origin at a micro pore.…”
Section: Fatigue Testssupporting
confidence: 73%
“…The tests are performed until a total number of 1×10 7 load cycles, because preliminary studies showed defect correlated specimen failure in the HCF region between 1×10 6 and 1×10 7 load cycles, see [3,48,49]. All evaluated S/N-curves are displayed including the 10 and 90 % probability of survival scatter band.…”
Section: Fatigue Testsmentioning
confidence: 99%
“…Amongst others, the effective projected area of the most critical defect perpendicular to the load direction as well as the minimal and maximal distance to the surface are investigated by means of scanning-electron and digital optical microscopy. Further information about this methodology is given in [34]. Subsequently, the relevant geometrical characteristics, such as the equivalent circle diameter deq, are derived (see Equation (3)).…”
Section: Resultsmentioning
confidence: 99%
“…The coefficient C1 is proposed to be 1.56 for interior subsurface defects, and 1.43 for surface defects [33]. Hence, surface intersecting defects are considered to be more fatigue-sensitive, even in the presence of larger interior defects, which is in line with preliminary studies [34,35]. Additionally, the Vickers hardness (HV) of the assessed material is used as a base material strength parameter [36,37].…”
Section: Introductionmentioning
confidence: 94%
“…Since a preliminary study in [56] revealed that the area parameter correlates well with the stress field around the inhomogeneity, this parameter is further utilized in this work for the estimation of defect sizes. The defect size measurement methodology invoked in this work is in detail described in [57,58,59]. According to investigations in [60,61], the statistical distribution of defect sizes can be characterized by the limiting extreme value distribution of the Lognormal (LN) distribution, namely the Gumbel or Extreme Value type one distribution (EV) [62,63].…”
Section: Introductionmentioning
confidence: 99%